A new mycobacterial rifampicin resistance - Motsi, Tatenda Shungu (My University, 2011)
Rifampicin is a major chemotherapeutic agent used against mycobacterial and nocardial infections. However, drug resistance in many of these strains has emerged as a one of the major challenges being faced by researchers. High level resistance to rifampicin is primarily due to mutational alterations in the rpoB gene encoding the β subunit of RNA polymerase. A number of cases have been reported in which there is no mutation in this gene leading to the discovery of the inactivation methods: decomposition, ADP-ribosylation, glucosylation and phosphorylation. Decomposition occurs mostly in Nocardia, Rhodococcus and Mycobacterium species. I isolated a new rifampicin resistance gene isolated from the M. smegmatis 43756Km1. Its sequence showed that it coded for the enzyme 2-hydroxy-6-ketonona-2,4-dienedioic acid hydrolase. This enzyme takes part in the hydrolysis of C-C bonds of aromatic compounds especially in the metabolic pathway of phenylalanine. Rifampicin is bright red but is completely decolourised by iri-mediated decomposition but 2-hydroxy-6-ketonona-2,4-dienedioic acid hydrolase showed only 75% decolourisation. This may be because this enzyme does not completely breakdown the rifampicin molecule.